Aplikasi Kurikulum 2013 berbasis Web dan Android - Pizaini, Pizaini; Affandes, Muhammad; Khonofi, Khoidir; Syarifuddin, Syarifuddin; Saputra, Kana (Fakultas Sains dan Teknologi, Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
To facilitate the assessment and application of Curriculum 2013 (K13) for schools, students and teachers need an application system that can be accessed via the web and mobile. This study builds applications with K13 standards in education units. This application can be accessed through web and mobile applications with centralized data based on the Application Programming Interface (API). This application was built with the interaction between teachers, students, parents with the method of system design, implementation and testing. The application is equipped with Telegram API-based notifications to inform parents and students of grades. This application runs well on web and mobile-based with a response of 84.7% of users stating that they strongly agree with the application's features.